2014
DOI: 10.1016/j.jtbi.2014.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the impact of decay in bed-net efficacy on malaria transmission

Abstract: Insecticide-treated nets (ITNs) are at the forefront of malaria control programs and even though the percentage of households in sub-Saharan Africa that owned nets increased from 3% in 2000 to 53% in 2012, many children continue to die from malaria. The potential impact of ITNs on reducing malaria transmission is limited due to inconsistent or improper use, as well as physical decay in effectiveness. Most mathematical models for malaria transmission have assumed a fixed effectiveness rate for bed-nets, which c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
34
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 46 publications
5
34
1
Order By: Relevance
“…Conversely, several other trials and mathematical studies show that bed net implementation alone is not the most advisable control measure() and could not even eliminate the disease, especially in highly endemic regions. () This is due to several factors, including improper handling and natural decline in efficacy over time, and also the interplay between ITNs and mosquito demography and feeding preferences . Furthermore, ITN success in malaria elimination could be (mathematically) hindered by the existence of a backward bifurcation,() which suggests that additional effort is required to eliminate the disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, several other trials and mathematical studies show that bed net implementation alone is not the most advisable control measure() and could not even eliminate the disease, especially in highly endemic regions. () This is due to several factors, including improper handling and natural decline in efficacy over time, and also the interplay between ITNs and mosquito demography and feeding preferences . Furthermore, ITN success in malaria elimination could be (mathematically) hindered by the existence of a backward bifurcation,() which suggests that additional effort is required to eliminate the disease.…”
Section: Introductionmentioning
confidence: 99%
“…() This is due to several factors, including improper handling and natural decline in efficacy over time, and also the interplay between ITNs and mosquito demography and feeding preferences . Furthermore, ITN success in malaria elimination could be (mathematically) hindered by the existence of a backward bifurcation,() which suggests that additional effort is required to eliminate the disease. In Agusto et al, it has been shown that if at least 75% of the population adopts bed nets, malaria could be eliminated, while the analysis of model presented in Dembele and Yakubu revealed that malaria remains endemic when not more than 80% of the population is protected from mosquito bites.…”
Section: Introductionmentioning
confidence: 99%
“…The threshold parameter scriptR is the equivalent of the vectorial and basic reproduction numbers in vector and epidemiological models (Van den Driessche & Watmough ; Ngonghala, Ngwa & Teboh‐Ewungkem ; Ngonghala, Teboh‐Ewungkem & Ngwa ; Ngonghala et al . ). Note that the equilibrium solutions of equation can also be obtained by setting the right‐hand side of the equation to zero and solving for x .…”
Section: Model and Analysismentioning
confidence: 97%
“…Female mosquitoes require blood meals to produce eggs and only anopheles mosquitoes transmit malaria. In order to transmit the disease, a female anopheles mosquito must have been infected in a previous blood meal from an infected person [15,18,24]. The disease remains a major burden in many parts of the world, with Africa and south-east Asia at high risk of malaria infection [36].…”
Section: Introductionmentioning
confidence: 99%
“…However, malaria is still of public health concern, with high mortality in children [36]. There is a wide range of malaria intervention strategies, some of which are: insecticide-treated nets [1,24], indoor residual spraying [34,36], anti-malarial drugs such as artemesinin combination therapy [32,36], and intermittent preventive treatment in children (IPTi) and in pregnant women (IPTp) [32]. Several studies have been conducted to investigate the efficacy and efficiency of these interventions as well as how best to integrate these control efforts in a fight against malaria (see [3,15,18,24,32,34] and references therein).…”
Section: Introductionmentioning
confidence: 99%